Therapeutic response to combination of oral isotretinoin and topical 0.1% tacrolimus ointment in lichen planus pigmentosus: A case series - Taru Garg; Riaz Ahmed; Anuja Rao; Vibhu Mendiratta (Pigment International)
Lichen Planus Pigmentosus (LPP) is a pigmentary disorder of unknown etiology, presenting with diffuse hyperpigmentation in sun-exposed areas. It is a cosmetically distressing pigmentary disorder often posing a therapeutic challenge. There are few reports showing efficacy of oral isotretinoin and topical tacrolimus in LPP. However combination of both these therapeutic modalities has not been described earlier. Herein we report a series of 10 patients who showed good response to combination of oral isotretinoin (20 mg/day) and topical 0.1% tacrolimus ointment.